(untitled) (FACE: Revista de la Facultad de Ciencias Económicas y Empresariales, 2022)
This article proposes a simulation methodology to forecast the spread of COVID-19 in Colombia, taking into account the virus dynamics in the country, aiming to identify when the number of infected patients in hospitals and intensive care units (ICUs) could exceed the capacity of the healthcare system. This methodology has been developed through the application of a simulation model (ISC-19) that allows projecting the number of COVID-19 cases in ICUs and hospitalization areas. Based on these projections, the risk of healthcare system saturation is evaluated according to the installed capacity of beds. The implementation of this methodology can alert decision-makers to develop strategies that can be implemented in the short term, either to reduce patient demand or to prevent a possible collapse of the healthcare system.